Effects of rainfall interception by sand-fixing vegetation on soil carbon and nitrogen distribution in a sand-covered hilly area - Xin, Wang; Zhenqi, Yang; Jianying, Guo; Li, Zhen; Fucang, Qin (Frontiers in Plant Science, 2025)
AimsThe landscape of sand-covered hilly areas has been reshaped by afforestation in these areas. Dynamic changes in soil moisture and nutrients in forests after afforestation have become evident. However, clear studies have not focused on whether rainfall interception in these plantations affects soil concentration or concentration.MethodsThis largely limits the development of effective management techniques for plantations and hinders the optimal utilization and management of water resources. In this study, an investigation was conducted on the plant community structure, rainfall interception characteristics, and soil organic carbon (SOC) and total nitrogen (N) concentrations or concentrations of three different plantations in the sand-covered hilly area of the Kuye River Basin. Grassland (Gl) was taken as the control.ResultsThe critical throughfall values for C. korshinskii (Ck), S. Cheilophila (Sc) and P. sylvestris (Ps) were 0.28, 1.78 and 2.04 mm, respectively. Corresponding stemflow critical values measured were 2.93, 1.08, and 3.30 mm, respectively. Ps exhibited the highest interception capacity, which was attributable to its dense canopy and layered branch architecture. Sc ranked second due to its larger leaf area, while Ck showed the lowest interception because of wide branch angles and smaller leaf area. Post-rainfall ground-level soil moisture and litter deposition are regulated by vegetation canopy structure in a direct way. SOC and N concentrations are subsequently controlled by these ground-level parameters. SOC concentration under Ps was 1.54 compared to that under Gl, while N concentration was 1.50 times higher, respectively.ConclusionsThus, Ps demonstrates optimal effectiveness for improving soil quality in sandy hill restoration areas and merits continued implementation in this region.